(4z + x²z) dz + (1+z²)dx - (yz² + y)(4+x²)dy=0
By Lagrange method,
"\\frac{dx}{1+z^2}=\\frac{dy}{- (yz\u00b2 + y)(4+x\u00b2)}=\\frac{dz}{4z+x^2z}\\\\"
By taking the first equation,
"\\frac{dy}{- (yz\u00b2 + y)(4+x\u00b2)}=\\frac{dz}{4z+x^2z}\\\\\n\\frac{dy}{- y(z\u00b2 + 1)(4+x\u00b2)}=\\frac{dz}{z(4+x^2)}\\\\\n\\frac{dy}{- y}=(\\frac{1}{z}+z)dz\\\\"
Integrating both sides,
"-lny=lnz+\\frac{z^2}{2}+c\\\\\nln(\\frac{1}{yz})-\\frac{z^2}{2}=c"
And, from the second equation,
"\\frac{dx}{1+z^2}=\\frac{dz}{4z+x^2z}\\\\\n\\frac{dx}{1+z^2}=\\frac{dz}{z(4+x^2)}\\\\\n(4+x^2)dx=(\\frac{1}{z}+z)dz\\\\\n4x+\\frac{x^3}{3}=lnz+\\frac{z^2}{2}+c\\\\\n4x+\\frac{x^3}{3}-lnz-\\frac{z^2}{2}=c"
Thus, the general solution is given by
"F(ln(\\frac{1}{yz})-\\frac{z^2}{2}, 4x+\\frac{x^3}{3}-lnz-\\frac{z^2}{2})=0"
Comments
Leave a comment